2022
DOI: 10.3389/fgene.2022.835265
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of YTHDF1 Immune Infiltrates and ceRNA in Human Esophageal Carcinoma

Abstract: Background: YTHDF1 is highly expressed in multiple tumors and affects tumor progression. However, there are only a few comprehensive studies on the analysis of YTHDF1 in esophageal cancer.Methods: We analyzed YTHDF1 expression in pan-cancer by comparing both the GEPIA and TCGA cohorts, and further verified the differences in YTHDF1 expression between the ESCA and normal groups by the GEO ESCA cohort and in vitro experiments. The correlation of YTHDF1 expression and the clinical characteristics of ESCA patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 70 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…In esophageal cancer (ESC), YTHDF1 is highly expressed and correlated with multiple adverse clinical features [ 93 ]. LncRNA-HCP5 directly interacts with YTHDF1 and promotes m6A-modified HK2 mRNA translation, thereby boosting the Warburg effect of ESC cells, and ESC progression [ 73 ].…”
Section: Introductionmentioning
confidence: 99%
“…In esophageal cancer (ESC), YTHDF1 is highly expressed and correlated with multiple adverse clinical features [ 93 ]. LncRNA-HCP5 directly interacts with YTHDF1 and promotes m6A-modified HK2 mRNA translation, thereby boosting the Warburg effect of ESC cells, and ESC progression [ 73 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the sum of the correlations of these 385 genes in gastrointestinal cancer, we screened the 30 genes with the strongest correlations, which are RARS1, BTF3, HSPA4, NSA2, HNRNPA1, EIF3M, CCT4, OLA1, UIMC1, G3BP1, NACA, RSL1D1, ETF1, MRPS27, RBM22, CCT8, GEMIN5, LARS1, PA2G4, CDK7, NIFK, RSL24D1, EIF3E, THG1L, INTS13, UBE2D2, RPS23, DIMT1, RIOK2, and TTC27 respectively. Previous studies have reported that overexpression of BTF3, CCT8, CDK7, ELF3M, G3BP1, HSPA4, OLA1, and RSL1D1 can contribute to the occurrence and development of CRC ( Goh et al, 2011 ; Zhou et al, 2019 ; Zhou et al, 2021b ; Liao et al, 2021 ; Zhang et al, 2021 ; Liu et al, 2022a ; Liu et al, 2022b ; Li et al, 2022 ), overexpression of CCT4 and PA2G4 can contribute to the occurrence and development of LIHC( Li et al, 2021a ; Sun et al, 2022 ), overexpression of DIMT1 and HNRNPA1 can contribute to the occurrence and development of STAD ( Liu et al, 2017 ; Zhu et al, 2022 ), and overexpression of EIF3E and UIMC1 can contribute to the ESCA occurrence and development ( Xu et al, 2018 ; Yang et al, 2018 ). Therefore, we believe that these genes have the potential to be called diagnostic and therapeutic targets of gastrointestinal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have focused on the tumor immune microenvironment ( 36 , 37 ). Pyroptosis regulates the tumor immune microenvironment through various mechanisms.…”
Section: Discussionmentioning
confidence: 99%